2016
DOI: 10.1017/s0007114516001033
|View full text |Cite
|
Sign up to set email alerts
|

A nutrition intervention is effective in improving dietary components linked to cardiometabolic risk in youth with first-episode psychosis

Abstract: Severe mental illness is characterised by a 20-year mortality gap due to cardiometabolic disease. Poor diet in those with severe mental illness is an important and modifiable risk factor. The present study aimed to (i) examine baseline nutritional intake in youth with first-episode psychosis (FEP), (ii) evaluate the feasibility and acceptability of nutritional intervention early in FEP and (iii) to evaluate the effectiveness of early dietary intervention on key nutritional end points. Participants were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 44 publications
4
40
0
Order By: Relevance
“…These workshops were very popular and showed successful preliminary outcomes (20). A recent study reported that a nutrition intervention in youth with first-episode psychosis successfully improved their dietary behaviors, particularly reduced intake of discretionary foods high in fat and sugar, and increased vegetable intake that is associated with reduced CVD risk (21). …”
Section: Discussionmentioning
confidence: 99%
“…These workshops were very popular and showed successful preliminary outcomes (20). A recent study reported that a nutrition intervention in youth with first-episode psychosis successfully improved their dietary behaviors, particularly reduced intake of discretionary foods high in fat and sugar, and increased vegetable intake that is associated with reduced CVD risk (21). …”
Section: Discussionmentioning
confidence: 99%
“…The seminal works of Teasdale et al . (, ) highlight for youth with first‐episode psychosis that tailored dietetic consultation can reduce cardiometabolic risk (Teasdale et al . ) and improve diet quality (Teasdale et al .…”
Section: Discussionmentioning
confidence: 99%
“…Teasdale et al . , ). Therefore, strategies to improve access to APD healthcare provision for adults with SMI attending community mental health services (CMHS) are only barely known.…”
Section: Introductionmentioning
confidence: 97%
“…The etiology of cardiovascular disease as relevant to schizophrenia is multifactorial and complex, with antipsychotic medications (Peet, 2004), increased incidence of smoking (McCreadie, 2003; Hennekens et al, 2005), unhealthy dietary and excess sodium intake (Brown et al, 1999; Teasdale et al, 2016), sedentary behavior (McCreadie et al, 1998), each having a substantial role. The primary cardiovascular disease risk markers that are routinely investigated in schizophrenia include metabolic syndrome, Framingham 10-year Relative Risk score, C-reactive protein, and dyslipidemia.…”
Section: Schizophrenia and Cardiovascular Diseasementioning
confidence: 99%
“…A similar nutritional intervention conducted in a first episode schizophrenia patient sample was effective at reducing excessive sodium and caloric intake observed at study baseline (Teasdale et al, 2016). While the DASH diet and other sodium intake reduction measures are quite effective at reducing hypertension and inflammation, compliance has been suboptimal in various clinical populations (Feyh et al, 2016; Teasdale et al, 2016). Successful implementation of the DASH or modified DASH diet to target hypertension or other cardiovascular risk factors will require cognitive and behavioral modification strategies to maintain adherence in schizophrenia spectrum populations.…”
Section: Schizophrenia Empirically Based Diets and Nutritional Suppmentioning
confidence: 99%